2021
DOI: 10.1007/s00216-021-03675-z
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Determination of organically bound fluorine sum parameters in river water samples—comparison of combustion ion chromatography (CIC) and high resolution-continuum source-graphite furnace molecular absorption spectrometry (HR-CS-GFMAS)

Abstract: A Correction to this paper has been published: 10.1007/s00216-021-03675-z

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although results obtained with the two different instruments are comparable (Gehrenkemper et al 2021), HR-GFMAS analysis has been found to be more sensitive and less time consuming (Gehrenkemper et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although results obtained with the two different instruments are comparable (Gehrenkemper et al 2021), HR-GFMAS analysis has been found to be more sensitive and less time consuming (Gehrenkemper et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing amounts of GenX have been detected in drinking water and soil (Gebbink and van Leeuwen 2020 ). In 2015, GenX contamination was discovered near the Cape Fear River in North Carolina, downstream of a chemical manufacturing company (Cahoon 2019 ).…”
Section: Introductionmentioning
confidence: 99%